Optimisation and dynamic simulation of a conveying and top breaking system for whole-stalk sugarcane harvesters. (September 2020) - Xie, Luxin; Wang, Jun; Cheng, Shaoming; Zeng, Bosheng; Yang, Zizeng
Abstract : One of the critical barriers for whole-stalk sugarcane mechanical harvesting is the high proportion of impurities especially in the cane tops. In this study, a whole-stalk sugarcane conveying and top breaking system was developed and tested to improve top breaking performance. Effects of feeding roller speed, top breaking roller speed, stagger angle of upper and lower top breaking elements and distance between the upper and lower top breaking element on sugarcane top breaking rate, non-fracture rate and power requirement were explored. Central composite design combined with response surface method was employed to conduct experiments and explore the interaction effects of influence factors on indicators. The optimal structure and operating parameters were determined to be 305 rpm for feeding roller speed, 520 rpm for top breaking roller speed, 14° for the stagger angle and 10 mm for the distance. The predicted values for top breaking rate, non-fracture rate and power requirement were 85%, 83% and 690 W, respectively. Verification experiments demonstrated that the observed values were in agreement with the predicted values. Based on the optimised results, a rigid-flexible coupling model was established for sugarcane conveying and top breaking and the simulation results showed that the model was reliable in predicting the kinetic characteristics of sugarcane in conveying and top breaking processes. The maximum resultant striking force of the top breaking elements on the cane stalk was 807.68 N. Overall, the conveying and top breaking system developed in this study was effective for improving top cleaning performance in whole-stalk sugarcane harvesting. Highlights: Sugarcane top breaking parameters were optimised using central composite design. Estimating sugarcane top breaking characteristics through simulation analysis. The conveying and top breaking system improved sugarcane top cleaning performance.